Anti‐Environmental Aging Passive Daytime Radiative Cooling - Jianing Song; Qingchen Shen; Huijuan Shao; Xu Deng (Advanced Science, 2024)
Abstract Passive daytime radiative cooling technology presents a sustainable solution for combating global warming and accompanying extreme weather, with great potential for diverse applications. The key characteristics of this cooling technology are the ability to reflect most sunlight and radiate heat through the atmospheric transparency window. However, the required high solar reflectance is easily affected by environmental aging, rendering the cooling ineffective. In recent years, significant advancements have been made in understanding the failure mechanisms, design strategies, and manufacturing technologies of daytime radiative cooling. Herein, a critical review on anti‐environmental aging passive daytime radiative cooling with the goal of advancing their commercial applications is presented. It is first introduced the optical mechanisms and optimization principles of radiative cooling, which serve as a basis for further endowing environmental durability. Then the environmental aging conditions of passive daytime radiative cooling, mainly focusing on UV exposure, thermal aging, surface contamination and chemical corrosion are discussed. Furthermore, the developments of anti‐environmental aging passive daytime radiative cooling materials, including design strategies, fabrication techniques, structures, and performances, are reviewed and classified for the first time. Last but not the least, the remaining open challenges and the insights are presented for the further promotion of the commercialization progress.